The Power of Partnerships in Becoming Accountable for the Impact of Teacher Candidates on P-12 Learning - Pankratz, Roger (Educational (Re)naissance, 2012)
The “Renaissance Partnership”, a consortium of eleven universities and their partner schools, was one of the first twenty-five Teacher Quality Enhancement Projects funded in 1999. The Project’s two primary goals, “to become accountable for the impact of teacher graduates on the students they teach” and “to institutionalize reforms in preparation programs,” to a great extent have been achieved. Successes are attributed to “the power of partnerships.” This paper provides a brief account of the development of the Renaissance Partnership and the struggles to achieve project objectives, a description of project achievements, a third party evaluator’s summary and, finally, a project director’s reflections and conclusions.